STRATEGI BISNIS ONLINE SALAD BUAH DL DI MAJENE MELALUI VALUE CO-CREATION PADA MASA PANDEMI COVID-19 - Mutiara Ulpa (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Regulations set by the government due to the transmission of Covid-19 have a major impact on entrepreneurial activities, especially for small business actors. Innovation and creativity in product marketing to create shared value with consumers is a solution in adaptation during the Covid-19 pandemic and as a strategy to stabilize the economy. The purpose of this study was to describe the condition of the food business during the pandemic in Majene City, to describe the problems experienced by the DL Fruit Salad food business, especially during the covid-19 pandemic, to describe the value co-creation that emerged in the DL Fruit Salad food business and to create a model. problem solving against obstacles from the DL Fruit Salad food business. This research method uses a qualitative approach with purposive sampling in sample selection. Keywords: Strategy,Business,Online, Value Co Creation